Real Time DC Motor Position Control Using PID Controller in LabVIEW - Khalifa, Mustafa; Amhedb, AL Hussein; Al Sharqawi, Mohammed (Journal of Robotics and Control (JRC), 2021)
Direct current (DC) motors are the most used motors in control engineering applications due to their simplicity of construction, easy to control, and excellent performance. These motors should be well controlled to perform the required task. This research focuses on DC motor functional application in terms of a position control system using LabVIEW. This control system is a closed-loop real-time control system whereas incremental encoder 298 is coupled to the motor shaft to provide the feedback position signal to a controller; Proportional Integral Derivative (PID) The PID controls the position of the DC motor at the desired position with a minimum error. The PID controller was implemented in LabVIEW software which sends the control signal to the real-time DC motor through the Arduino board. In addition, LabVIEW software was developed to show the output response of motor position versus time to easily observe the performance of the system. The PID controller gains were obtained based on the trial and error method. The system under these controller parameters has been tested at different positions of tracking signal and for disturbance rejection. Finally, the results showed that the designed controller had good performance characteristics where the desired position of the motor was maintained.